Kurds, Islam, and Secularism - Meirison Meirison (Jurnal Madania, 2019)
The Kurds, a tribe that follows the Shafi’i madhhab (one of the four schools of Islamic law), obey and adhere to the Islamic Sharia. This tribe, however, has changed the course since secularism occurred in Turkey. The Kurds lost their way because the leader in charge was the Sultan of Turkey as the representative of Muslims.  In the past, the principles of Islam were still carried out by the Kurds, say they believed that all people were born equal in the sight of Allah and the only characteristic that made someone superior to another is righteousness (al-taqwa). Nowadays, this belief is no longer embraced. This study aims to capture Kurdistan figures from various dimensions such as history, social and politic. Due to the political ruins of World War I and II,  the Kurdish has had a big ambition for independence. They have suffered from agitation, intimidation, and massacres given by neighboring countries. Consequently, this leads  the Kurds to become weak and unsteady among anti-Islam  ideologies such as marxism, leninism, and radical secularism.